Coffee and cocoa: the wheel of fortune turns for the international markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
1992 will go down in history as the worst year since World War II for the prices of coffee and cocoa, two major tropical agricultural exports. But 1993 will be remembered for the spectacular come-back in price levels and a fundamental restructuring...